Dendritic glycopolymers as dynamic and covalent coating in capillary electrophoresis: View on protein separation processes and detection of nanogram-scaled albumin in biological samples - Polikarpov, Nikita; Potolytsyna, Vera; Bessonova, Elena; Tripp, Sandra; Appelhans, Dietmar; Voit, Brigitte; Kartsova, Ludmilla (Journal of Chromatography A, 2015)
Unique properties of dendritic polymers make them promising candidates for application as additives in various analytical methods. From this point, we investigated the potential use of maltose-modified hyperbranched poly(ethylene imine) (PEI-Mal) as a dynamically or covalently bound coating and a pseudostationary phase in capillary electrophoresis. The EOF mobilities were measured at different pH values (2.2, 8.5, and 10.2) using PEI-Mal in the background electrolyte (BGE) and desirable repeatability of the EOF with % RSD (. n=. 50) ≤3.3 was obtained. The influence of pH, polymer concentration, and density of maltose shell on the separation properties of a model mixture of four proteins (albumin, lysozyme, myoglobin, insulin) were investigated. Applying PEI-Mal as a dynamic coating, improved separation of the protein mixture with a high repeatability was achieved. Applying PEI-Mal as a covalent coating for concentrating proteins in the large volume sample stacking (LVSS) combined with the field-enhanced sample injection (FESI), up to 1320-fold enhancement of sensitivity was achieved. The detection limit of 100-500. ng/ml allowed successful analysis of albumin level both in blood and urine samples without additional preconcentration.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Capillary electrophoresis; Covalent coating; Dynamic coating; Hyperbranched polymers; On-line concentration; Proteins